2021
DOI: 10.1111/1365-2745.13594
|View full text |Cite
|
Sign up to set email alerts
|

Tropical deforestation reduces plant mating quality by shifting the functional composition of pollinator communities

Abstract: Deforestation can impact the quality of pollen received by target plants (i.e. delivery of incompatible pollen, self‐pollen or pollen from closely related individuals). Such reductions in plant mating quality may be direct, when deforestation reduces plant population size and the availability of pollen donors, or indirect, when decreased mating quality results, for example, from shifts in the composition of the pollinator community. As most flowering plants depend on animal pollinators for reproduction, there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 110 publications
3
11
0
Order By: Relevance
“…Determining whether this is the case is important for two reasons. First, we agree with Betts et al [18] that filtering the short-billed, territorial hummingbirds could promote outcrossing and enhance the genetic diversity of pollen grains that reach the ovules, a hypothesis that is supported by landscape genetic studies of H. tortuosa populations in Costa Rica [9,10]. Given the potential for fitness benefits, pollinator recognition could be present in many related taxa and could be one means through which tight morphological matching evolves despite apparently generalized interaction networks.…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…Determining whether this is the case is important for two reasons. First, we agree with Betts et al [18] that filtering the short-billed, territorial hummingbirds could promote outcrossing and enhance the genetic diversity of pollen grains that reach the ovules, a hypothesis that is supported by landscape genetic studies of H. tortuosa populations in Costa Rica [9,10]. Given the potential for fitness benefits, pollinator recognition could be present in many related taxa and could be one means through which tight morphological matching evolves despite apparently generalized interaction networks.…”
Section: Introductionsupporting
confidence: 91%
“…This would be adaptive if plants suffer from inbreeding depression. Indeed, Torres-Vanegas et al [21,52] found genetic signatures in H. tortuosa populations that are consistent with this hypothesis; inbreeding was greatly reduced in large, connected forest patches where morphologically matched, traplining hummingbirds were more prevalent. In H. rostrata styles, visits from clean hummingbirds to hand-pollinated flowers also increased pollen tube rates, but regardless of the bird species.…”
Section: Implications Of Pollinator Recognitionmentioning
confidence: 72%
“…When markers were designed and modified from the above studies (Table S1), primer combinations showing evidence of null alleles were eliminated from the genotyping panel. Furthermore, mother–offspring arrays examined in a separate study using the same marker system and individuals from many of the same forest patches did not reveal the presence of null alleles (Torres‐Venegas et al 2019, Torres‐Vanegas et al, 2021). Finally, to confirm the absence of null alleles, analyses using the program inest , which jointly estimates null allele frequency and inbreeding levels, were conducted (Chybicki & Burczyk, 2009) for all individual populations in our study.…”
Section: Methodsmentioning
confidence: 94%
“…Furthermore, a recent study has shown that the relative abundance of traplining birds can affect both the mating system and levels of genetic diversity of H. tortuosa seeds. Higher abundances of traplining birds within stands are correlated with increased pollen pool genetic diversity and lower levels of biparental inbreeding in predispersed ungerminated embryos inferred from mother-offspring genotype arrays (Torres-Vanegas et al, 2021). However, additional factors affecting genetic diversity should be studied, such as the persistence of genetic diversity through later juvenile and adult life stages, differences between populations in primary and secondary forest patches, and the impact of landscape variables and bird community species composition.…”
Section: Introductionmentioning
confidence: 99%
“…Pollen quantity can be measured by counting conspecific pollen grains delivered to a stigma during a single visit (‘single‐visit deposition’: King et al ., 2013; Ballantyne et al ., 2015), while pollen quality depends on numerous plant‐specific variables (e.g. genetic compatibility, relatedness, presence of multiple sires) and is best ascertained through seed set (Ne’eman et al ., 2010; Santiago‐Hernández et al ., 2019) or genetic measures (Torres‐Vanegas et al ., 2021). Additionally, in plant species with pollinator filtering mechanisms (i.e.…”
Section: Ecological Relationships Between Hummingbirds and Plantsmentioning
confidence: 99%